APPROVAL OF FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE OPERATORS IN INFORMATION PROCESSING AND SOFTWARE - GAZDYK, Myroslava (Social work and education, 2024)
The article is devoted to the problem of researching the effectiveness of the process of forming the professional competence of future information processing and software operators in the process of professional training. It was found that the system of training future specialists in the process of professional training is aimed at ensuring their readiness for professional activity, taking into account all components of the educational process of the educational institution. It was clarified that the important factors of the problem of the formation of professional competence of future specialists in the process of professional training are inadequate readiness for professional activity and the appropriate level of their professional competence for such activity. It was revealed that the process of formation of professional competence of individuals for professional activity is influenced by the following factors: transformation of the content of training of future operators in information processing and software in professional (vocational and technical) education institutions; the prestige of the profession and its social significance; professional development and development of the personality of future specialists; acquisition of practical experience by students of education regarding the implementation of innovative technologies and project activities; purposeful mastery of professional skill and specialty; the formation of a culture of mastery and the readiness of qualified specialists for professional activity. It is specified that the formation of professional competence of future specialists in the process of professional training is oriented towards: purposeful formation of a complete system of professional competences in the process of professional training; development of motivational potential; enrichment of the development of individual and professional qualities, formation of self-assertion, improvement of personal and professional assets, acquisition of one's own style of work; accumulation of experience in professional skills for effective performance of professional activities, improvement of professional abilities and skills for further self-actualization, self-improvement of professional activities, development of quick adaptation to full-fledged future activities; improvement of assets of creative and scientific research, enabling professional self-development in professional activity. The study of the continuity of the development of future specialists to professional activity requires further development.